Receiving the Coronavirus Vaccine while Fasting (a Comparative Study between the Fatwa of the MUI and World Fatwa Councils) | أخذ لقاح فيروس كورونا أثناء الصيام (دراسة مقارنة بين فتوى مجلس العلماء الإندونيسي ومجالس الإفتاء في العالم الإسلامي) - Yuli Yasin; Muhammad Zein Rizky (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2021)
This research aims to know the ruling on the validity of fasting by receiving a vaccine for the Coronavirus or not, through the fatwa of the Indonesian Council of Scholars, compared to the fatwas of the fatwa councils in the Islamic world, using the analytical and comparative methodology.Fasting is obligatory for Muslims in the month of Ramadan in particular, and it may be required in other months. On the other hand, the Coronavirus may spread in the world at the end of the year 2019. As of February 28, 2021, it has recorded one million and 335 thousand infections and 36 thousand and 166 deaths, and in Indonesia, which leads the government to take preventive measures, including positively receiving the Coronavirus vaccine for the people. And when Ramadan came, people were wondering about the ruling on taking it while fasting, and the Fatwa Committee of the Indonesian Council of Scholars issued a fatwa that fasting is not invalidated by receiving the vaccine, and it became clear that this fatwa agrees with the fatwas of the fatwa councils in the Islamic world.